1996
DOI: 10.1007/s004410050668
|View full text |Cite
|
Sign up to set email alerts
|

New light on the cell location of avarol within the sponge Dysidea avara (Dendroceratida)

Abstract: Many sponges produce and store secondary metabolites with interesting pharmacological bioactivities. Identification of the cell type(s) responsible for the production and/or storage of these compounds may be a crucial step for the future culture and production of these substances if the biosynthesis is not envisageable and the producer organism is rare or too slow-growing for feasible exploitation. Localisation of these cells within the sponge may also contribute to ascertaining the ecological role of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…Intrigued by the wide range of biological activities of these metabolites and the fact that avarol (1) is biosynthesized in large amounts by the sponge, implying an important ecological role [36], we decided to investigate their antifouling activity and prepare a number of lipophilic derivatives that would reduce their solubility in sea water and improve their incorporation in a potential antifouling preparation. …”
Section: Resultsmentioning
confidence: 99%
“…Intrigued by the wide range of biological activities of these metabolites and the fact that avarol (1) is biosynthesized in large amounts by the sponge, implying an important ecological role [36], we decided to investigate their antifouling activity and prepare a number of lipophilic derivatives that would reduce their solubility in sea water and improve their incorporation in a potential antifouling preparation. …”
Section: Resultsmentioning
confidence: 99%
“…It is the natural source of avarol and related metabolites that have shown antitumoral, antibacterial, antiviral, and anti-inflammatory activities (Müller et al 1985;Minale et al 1974;Uriz et al 1996). Avarol is currently being tested on humans in Germany as an additive to a skin cream for treating psoriasis (Pietschmann et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14 Other recent studies of metabolite localization in sponges demonstrate that major secondary metabolites are often not found in the symbionts. 16 " 17 ' 251 " 254 Cell fractionation and Ehrlich staining showed that the defensive furanosesquiterpenes found in Dysidea fragilis were located in large spherular sponge cells. 253 Cell fractionation on Ficoll gradients showed that avarol 62 from Dysidea avara was located within choanocytes.…”
mentioning
confidence: 99%